Civic Education at Public Islamic Higher Education (PTKIN) and Pesantren - Azyumardi Azra (TARBIYA: Journal of Education in Muslim Society, 2015)
With a brief foundation that covers some reviews of world literature on education and politics, the study points out the significance of developing a certain model of democracy education in the diverse country, Indonesia. The paper aims to establish the development and the excavation of democracy in Indonesia by presenting historical explanation on how Indonesian muslim scholars from UIN Syarif Hidayatullah Jakarta developed a suitable model of Indonesian civic education, which considers the elements of diversity as strengthening elements for democracy. Different from Shanker’s view (1996) on the global challenge of civic education, this study shows the successful experience of Indonesian Muslim in the development and application of civic education as a compulsory subject in Islamic education institutions, namely Public Islamic Higher Education (PTKIN) and pesantren. Finally, it recommends further development and emphasizes the vital influence on rooting civic education in Pesantren since it will positively play an important role to strengthen the evolving democracy in Indonesia by integrating Islamic and Indonesian values. Abstrak Dengan melakukan review singkat terhadap beberapa literatur internasional tentang pendidikan dan politik, studi ini menunjukkan pengembangan model khusus  pendidikan demokrasi di Indonesia sebagai negara multi etnis. Tulisan ini bertujuan untuk menggambarkan perkembangan dan pengembangan demokrasi di Indonesia dengan pemaparan historis  tentang bagaimana muslim Indonesia khususnya di UIN jakarta dalam mengembangkan model Civic Education yang tepat, yang mempertimbangkan  elemen keberagamaan sebagai penguat demokrasi. Berbeda dari pendapat Shanker(1996) tentang tantangan global terhadap pendidikan kewarganegaraan, studi ini menggambarkan pengalaman sukses muslim Indonesia dalam mengembangkan pendidikan kewarganegaraan sebagai mata kuliah wajib di institusi pendidikan Islam dengan nama Perguruan Tinggi Keagaamaan Islam Negeri (PTKIN) dan Pesantren. Di bagian akhir, tulisan ini merekomendasikan pengembangan lebih jauh dan penekanan akan pentingnya pengaruh pendidikan kewarganegaraan di Pesantren, karena Pesantren memainkan peran penting untuk menguatkan pengembangan demokrasi di Indonesia dengan mengintegrasikan nilai-nilai keislaman dan keindonesiaan.How to Cite : Azra, A. (2015). Civic Education at Public Islamic Higher Education (PTKIN) and Pesantren. TARBIYA: Journal of Education In Muslim Society, 2(2), 167-177. doi:10.15408/tjems.v2i2.3186. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i2.3186